2006
DOI: 10.1002/app.23979
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on gradient dielectric characteristics of bamboo (Dentroclamus strictus)

Abstract: Dependence of dielectric constant (Ј) and dielectric dissipation factor (tan ␦) on distance from outermost skin to the center of bamboo has been determined. Dielectric measurements have been done in the temperature range of 24 -120°C and in the frequency range, 4 -100 kHz. Gradient behavior in Ј and tan ␦ has been found in bamboo. It has also been observed that Ј and tan ␦ increase with increasing temperature and decrease with increasing frequency. Relaxation times have been calculated for the four samples at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Bamboo is an economic forest and covers an area of 3.19 million hm 2 in China. In bamboo utilization industry, fractions of bamboo green, bamboo yellow, bamboo node, and bamboo branches are discarded due to the weakness in mechanical properties, generating approximately 46 million tons processing residues annually (Chand et al, 2006). However, only a part of these bamboo residues are burned to recover energy in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo is an economic forest and covers an area of 3.19 million hm 2 in China. In bamboo utilization industry, fractions of bamboo green, bamboo yellow, bamboo node, and bamboo branches are discarded due to the weakness in mechanical properties, generating approximately 46 million tons processing residues annually (Chand et al, 2006). However, only a part of these bamboo residues are burned to recover energy in industry.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chand et al (2006), bamboo stem is composed of bamboo skin, timber, and pith. There no vascular bundles exist in bamboo skin (the outer part) and pith (the inner part).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that nano grain structured fi bers are not brittle (Zou et al 2009 ). A continuous increase in hardness from center to outer surface is observed (Chand et al 2006 ). Hardness of bamboo fi bers is same in longitudinal as well as transverse directions.…”
Section: Hardnessmentioning
confidence: 82%